Photopolymerization rapid prototyping transparent medical hydrogel patch and preparation method thereof
Through the rapid photopolymerization molding method, hydrogel patches are prepared using vinyl monomers, and polymerization molding is performed using ultraviolet light (UV), which solves the low production efficiency and high energy consumption in the existing hydrogel patch preparation methods. Problem, rapid molding and efficient production are achieved.
Patent Information
- Application Number
- CN202411126687.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-02-14
AI Technical Summary
The existing preparation methods of hydrogel patches have problems such as solvent volatility, low production efficiency, high energy consumption, long refrigeration-thawing, inconvenient operation and difficulty in continuous production.
The photopolymerization rapid molding method is adopted, using vinyl monomer as raw material to prepare hydrogel patches through coating, and polymerization is carried out using ultraviolet light (UV) to achieve rapid molding.
The rapid molding of hydrogel patches is achieved, and the UV polymerization time only takes 5-15s, which improves the light polymerization efficiency, solves the problems of low production efficiency and high energy consumption in traditional methods, and supports continuous mass production.
Smart Images

Figure CN119424716A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of hydrogel dressings, and in particular to a photopolymerized rapid prototyping transparent medical hydrogel dressing and a preparation method thereof. Background Art
[0002] Hydrogel is a polymer material with a three-dimensional network structure and is insoluble in water. Its molecular network contains a large number of hydrophilic groups. Due to the existence of the cross-linked network structure, it can absorb a considerable proportion of water in an aqueous environment and has stable swelling and water retention. The degree of water absorption is related to the degree of cross-linking. As the degree of cross-linking increases, the water absorption performance gradually decreases. This property is very similar to soft biological tissue. Therefore, hydrogel has a wide range of applications in tissue engineering, drug release, wound healing and other fields due to its good biocompatibility.
[0003] Patent CN202311354524.6 discloses a hydrogel with acrylic acid as a monomer, adding a thermal initiator to the monomer prepolymer liquid and placing it in an oven to thermally initiate free radical polymerization. However, traditional thermally initiated polymerization will bring potential problems such as solvent volatilization, low production efficiency, and high energy consumption;
[0004] Patent CN202311636838.5 discloses injecting a hyaluronic acid mixed solution into a mold, freezing and thawing 1-5 times at -20°C, and using physical cross-linking to prepare a hydrogel. Freezing and thawing takes a long time, is inconvenient to operate, and has high requirements for equipment, making it difficult to produce continuously. Injection into the mold can easily lead to problems such as thick edges and thin middles.
[0005] Patent CN202211613091.7 discloses that some raw materials need to be stored at -80°C, which is a harsh storage condition; secondly, the prepolymer solution needs to be dissolved at 50°C and then injected into the mold, and the photopolymerization time takes 5-10 minutes, which is not conducive to continuous production and has low efficiency. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art, the present application provides a transparent medical hydrogel patch that can be quickly formed by photopolymerization and a preparation method thereof. The transparent medical hydrogel patch uses vinyl monomer as a raw material and is prepared by a coating method, which solves the problem of difficult leveling when injected into a mold and can be produced in continuous batches. The UV polymerization time of the present application is only 5-15s to be fully formed, and the efficiency of photopolymerization is significantly improved.
[0007] The technical solution adopted by this application to solve its technical problem is:
[0008] On the one hand, the present application provides a photopolymerized rapid-forming transparent medical hydrogel patch, comprising a hydrogel; the hydrogel is prepared by coating a prepolymer liquid containing ultraviolet light activity on a release film and then polymerizing and molding it through ultraviolet light irradiation.
[0009] Preferably, the prepolymer solution containing ultraviolet light activity comprises the following raw materials in parts by weight:
[0010] 10-45 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 5-30 parts of acrylamide, 5-10 parts of sodium acrylate, 5-10 parts of sodium styrene sulfonate, 0.15-1.5 parts of cross-linking agent, 0.01-0.1 parts of photoinitiator, 5-30 parts of moisturizing agent, 0.1-0.5 parts of preservative, and 0.01-0.2 parts of efficacy agent.
[0011] Preferably, the cross-linking agent is at least one of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate.
[0012] Preferably, the photoinitiator is at least one of TPO, Irgacure 2959 and LAP.
[0013] Preferably, the moisturizer is at least one of glycerin, propylene glycol and butylene glycol.
[0014] Preferably, the preservative is at least one of methylparaben, PHMB, benzethonium chloride and phenoxyethanol.
[0015] Preferably, the efficacy agent is at least one of sodium hyaluronate, menthyl ester, camellia extract, allantoin, and rose oil.
[0016] Preferably, the process of coating on the release film is to pour the prepolymer liquid containing ultraviolet light activity onto the conveyor belt of the coating equipment, and the thickness of the ultraviolet light activity prepolymer liquid is 0.5-3mm; after leveling, it is irradiated with ultraviolet light to form.
[0017] Preferably, the ultraviolet light irradiation polymerization molding is molding by ultraviolet light irradiation for 5-15s.
[0018] On the other hand, the present application provides a method for preparing a photopolymerized rapid prototyping transparent medical hydrogel patch, comprising the following steps:
[0019] S1. Preparation of prepolymer solution
[0020] Weigh the raw materials of the ultraviolet light active prepolymer solution by mass; dissolve 10-45 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 5-30 parts of acrylamide, 5-10 parts of sodium acrylate, and 5-10 parts of sodium styrene sulfonate in 100 parts of water to obtain a mixed solution A; adjust the pH of the mixed solution A to 7-10;
[0021] 0.15-1.5 parts of a crosslinking agent, 0.01-0.1 parts of a photoinitiator, 5-30 parts of a moisturizer, 0.1-0.5 parts of a preservative, and 0.01-0.2 parts of a functional agent are added to the pH-adjusted mixed solution A and dissolved to obtain a prepolymer solution containing ultraviolet light activity;
[0022] S2. Prepolymerization liquid coating
[0023] Pour the prepolymer liquid containing ultraviolet light activity onto the conveyor belt of the coating equipment, and the thickness of the ultraviolet light activity prepolymer liquid is 0.5-3mm; after leveling, it is irradiated with ultraviolet light to form;
[0024] S3. Molding
[0025] After being irradiated with ultraviolet light for 5-15 seconds, a semi-finished sheet of hydrogel is obtained;
[0026] S4. Die cutting
[0027] The semi-finished sheet of hydrogel is die-cut to obtain a transparent medical hydrogel patch.
[0028] The beneficial effects of this application are:
[0029] 1. The raw materials used in this application are simple and easy to obtain. They are common chemical raw materials for mass production on the market and do not require strict storage conditions;
[0030] 2. In the present application, the preparation of the prepolymer solution containing ultraviolet light activity can be completed at room temperature of 25°C, and can be quickly dissolved without heating, and avoids the problems of foaming and difficulty in coating caused by stirring of the viscous polymer prepolymer solution;
[0031] 3. This application uses UV polymerization for molding, which has the advantages of environmental friendliness, controllable polymerization, low energy consumption, and no solvent volatilization;
[0032] 4. In this application, the prepared hydrogel dressing is made of a fully transparent material. When used on the skin or wound, the skin healing condition can be directly observed, reducing the pain caused by changing the dressing;
[0033] 5. In the present application, the transparent medical hydrogel patch is prepared by coating using vinyl monomer as raw material, which solves the problem of difficult leveling when injected into the mold and can be produced in batches continuously. In addition, the UV polymerization time of the present application is only 5-15s to be fully formed, and the light polymerization efficiency is significantly improved.
[0034] 6. The transparent medical hydrogel patch described in the present application also has excellent cell compatibility, with a cell viability of up to 92%; it has good transparency, making it easier to observe the wound and skin recovery during use; it has excellent water retention and excellent air permeability. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The present application is further described below in conjunction with the accompanying drawings and embodiments.
[0036] Figure 1 This is a preparation flow chart of a method for preparing a photopolymerized rapid prototyping transparent medical hydrogel patch described in this application;
[0037] Figure 2 This is a schematic diagram of die cutting in the method for preparing a photopolymerized rapid prototyping transparent medical hydrogel patch described in the present application;
[0038] Figure 3 This is a photopolymerized rapid-prototyping transparent medical hydrogel patch described in the present application, attached to the skin surface of a volunteer;
[0039] Figure 4 The transparency of the photopolymerized rapid-molding transparent medical hydrogel dressing described in this application when applied to the wound surface;
[0040] Figure 5 This is a diagram showing the cell compatibility test results of a photopolymerized rapid prototyping transparent medical hydrogel patch described in the present application;
[0041] Figure 6 This is a comparison chart of the water retention performance of a photopolymerized rapid-forming transparent medical hydrogel dressing described in this application and several commercially available products;
[0042] Figure 7 This is a comparison chart of the air permeability of a photopolymerized rapid-prototyping transparent medical hydrogel dressing described in this application and several commercially available products. DETAILED DESCRIPTION
[0043] The following will clearly and completely describe the concept, specific structure and technical effects of the present application in combination with the embodiments and drawings, so as to fully understand the purpose, characteristics and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present application. In addition, all the connection / connection relationships involved in the patent do not simply refer to the direct connection of components, but refer to the formation of a better connection structure by adding or reducing connection accessories according to the specific implementation situation. The various technical features created in this application can be combined interactively without conflicting with each other.
[0044] like Figure 1 The photopolymerization rapid molding transparent medical hydrogel patch shown in the figure uses a monomer with a vinyl group as a raw material, adds a photoinitiator and a cross-linking agent, and prepares a prepolymer liquid with ultraviolet light activity; the prepolymer liquid is coated on a release film, and the surface is covered with a layer of anti-sticking film, and the sheet-like hydrogel is polymerized by ultraviolet light irradiation, and the obtained sheet-like hydrogel can be cut into patches of different shapes by a mold;
[0045] Specifically, the preparation method of the photopolymerized rapid prototyping transparent medical hydrogel patch comprises the following steps:
[0046] S1. Preparation of prepolymer solution
[0047] Weigh the raw materials of the ultraviolet light active prepolymer solution by mass; dissolve 10-45 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 5-30 parts of acrylamide, 5-10 parts of sodium acrylate, and 5-10 parts of sodium styrene sulfonate in 100 parts of water to obtain a mixed solution A; adjust the pH of the mixed solution A to 7-10;
[0048] Add 0.15-1.5 parts of a crosslinking agent, 0.01-0.1 parts of a photoinitiator, 5-30 parts of a moisturizer, 0.1-0.5 parts of a preservative, and 0.01-0.2 parts of a functional agent to the pH-adjusted mixed solution A and dissolve them to obtain a prepolymer solution containing ultraviolet light activity;
[0049] S2. Prepolymerization liquid coating
[0050] Pour the prepolymer liquid containing ultraviolet light activity onto the conveyor belt of the coating equipment, and the thickness of the ultraviolet light activity prepolymer liquid is 0.5-3mm; after leveling, it is irradiated with ultraviolet light to form;
[0051] S3. Molding
[0052] After being irradiated with ultraviolet light for 5-15 seconds, a semi-finished sheet of hydrogel is obtained;
[0053] S4. Die cutting
[0054] The semi-finished sheet of hydrogel is die-cut to obtain a transparent medical hydrogel patch.
[0055] In step S1, the crosslinking agent may be polyethylene glycol diacrylate or polyethylene glycol dimethacrylate. The photoinitiator is at least one of TPO, Irgacure 2959, and LAP. The moisturizer is at least one of glycerol, propylene glycol, and butylene glycol. The preservative is at least one of methylparaben, PHMB, and phenoxyethanol. The efficacy agent is at least one of sodium hyaluronate, menthyl ester, camellia extract, allantoin, and rose oil.
[0056] Specifically, 2-acrylamide-2-methylpropanesulfonic acid sodium salt: as one of the monomers, it provides the basic structure of the hydrogel. It contains hydrophilic groups, which contribute to the water absorption and water retention of the hydrogel. Acrylamide, which is often used in the preparation of hydrogels, can enhance the mechanical strength and stability of the hydrogel because it contains amide groups. Sodium acrylate, which contains sodium carboxylate groups, helps to improve the hydrophilicity and pH adjustment ability of the hydrogel. Sodium styrene sulfonate provides additional hydrophilicity and charge, which helps to improve the physical and chemical properties of the hydrogel.
[0057] Cross-linking agents (such as polyethylene glycol diacrylate, polyethylene glycol dimethacrylate) are used to form chemical bonds between monomers, strengthen the three-dimensional network structure of the hydrogel, and improve its mechanical strength and stability. Photoinitiators (such as TPO, Irgacure 2959, LAP): decompose under ultraviolet light to produce free radicals, initiate monomer polymerization, and quickly solidify the prepolymer solution into a hydrogel.
[0058] Moisturizers (such as glycerin, propylene glycol, and butylene glycol) help to maintain the moist state of the hydrogel, extend the service life of the hydrogel, and have a good moisturizing effect on the skin.
[0059] Preservatives (such as methylparaben, PHMB, benzethonium chloride, phenoxyethanol) are used to prevent microbial contamination of the hydrogel during storage and use to ensure the safety of the product.
[0060] Functional agents (such as sodium hyaluronate, menthyl ester, camellia extract, allantoin, rose oil) are used to provide specific therapeutic or health care functions. For example, sodium hyaluronate has the effects of moisturizing and promoting wound healing, and menthyl ester can have a cooling and soothing effect.
[0061] Therefore, a prepolymer liquid containing UV activity uses monomers with vinyl groups as raw materials, adds photoinitiators and cross-linking agents, and uses ultraviolet light (UV) as an initiation source to prompt the photoinitiator in the prepolymer liquid to quickly produce free radicals or ions, thereby initiating the monomers in the prepolymer liquid (such as acrylamide, sodium acrylate, etc.) to undergo a chain polymerization reaction. The prepolymer liquid containing UV activity has a fast photoinitiated polymerization reaction speed, can complete the construction of the three-dimensional network structure of the hydrogel in a short time, and achieve rapid molding.
[0062] In the present application, the transparent medical hydrogel patch uses UV polymerization, and the prepolymer liquid can form a hydrogel at room temperature in only 15 seconds at most, avoiding traditional physical cross-linking or heat-induced polymerization. Compared with other similar methods, the efficiency is greatly improved and it is more conducive to mass production.
[0063] Specifically, in step S3, the semi-finished sheet-shaped hydrogel is formed by ultraviolet irradiation for 5-15 seconds. The prepolymer liquid contains a photoinitiator, which will quickly decompose and generate free radicals under ultraviolet irradiation, initiating the monomers in the prepolymer liquid to undergo a polymerization reaction. At the same time, the thickness of the prepolymer liquid coating is controlled at 0.5-3 mm, so that the ultraviolet light can penetrate the prepolymer liquid more evenly, thereby achieving complete curing in a shorter time.
[0064] Example 1
[0065] A method for preparing a photopolymerized rapid-forming transparent medical hydrogel dressing comprises the following steps:
[0066] S1. Preparation of prepolymer solution
[0067] At room temperature, 10 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 10 parts of acrylamide, 5 parts of sodium acrylate, and 5 parts of sodium styrene sulfonate were placed in 100 parts of water, stirred and dissolved, and the pH was adjusted to 8.5 with citric acid; then 0.5 parts of polyethylene glycol diacrylate (as a cross-linking agent), 0.1 parts of TPO (as a photoinitiator), 5 parts of glycerol (as a moisturizer), 0.5 parts of methylparaben (as a preservative) and 0.1 parts of sodium hyaluronate (as a functional agent) were added in sequence, and the mixture was fully stirred and dissolved to obtain a prepolymer solution containing ultraviolet light activity.
[0068] S2. Prepolymer coating and molding
[0069] Pour the prepolymer liquid containing UV light activity onto the conveyor belt of the coating equipment at a uniform speed, place a release film underneath, and cover the upper surface with a layer of anti-sticking film. After leveling, irradiate with 365nm UV light for 15s to form. The UV light intensity is 90mw / cm 2 , coating thickness is 2mm.
[0070] S3. Die cutting
[0071] The semi-finished sheet of hydrogel obtained by coating is cut through a square mold to obtain a square patch (such as Figure 2 shown).
[0072] In the experimental test, the hydrogel prepared by the formula of Example 1 was used as the test sample. The test contents are as follows: (1) Cytotoxicity test
[0073] The cell compatibility test complies with GB / T 16886.5-2017 "Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Test" and is tested by the MTT extraction method; high-density polyethylene is selected as the negative control sample, and the test sample and negative control are placed in MEM culture medium containing 10% fetal bovine serum at 37°C for 72 hours. Then the sample extract is diluted to a certain concentration (100%, 50%, 25% and 12.5%). After L-929 mouse fibroblasts are cultured, the original culture medium is aspirated, and different concentrations of extracts and diluents are given respectively. After culturing in a 37°C, 5% carbon dioxide incubator for 24 hours, the culture medium is removed. After adding MTT solution and culturing for 2 hours, the MTT solution is removed. Add isopropanol solution for dissolution, and detect the absorbance at a wavelength of 570nm to calculate cell viability. The calculation formula is as follows:
[0074]
[0075] OD 570e is the mean absorbance of the test sample or control group; OD 570re is the mean absorbance of the blank control.
[0076] Table 1 Cell viability percentage test results of hydrogel samples
[0077]
[0078] GB / T 16886.5-2017 states that when the cell survival rate drops to <70% of the blank, it indicates potential cytotoxicity. Figure 5 As shown in Table 1, the cell activities of all groups of samples in the test samples were higher than 90%, indicating that the hydrogel prepared in Example 1 had good cell compatibility.
[0079] (2) Transparency
[0080] By sticking the hydrogel sample on the patient's wound skin, the patient's wound outline and the recovery of the red and swollen part of the wound can be clearly seen. Figure 3-4 shown.
[0081] (3) Water retention performance
[0082] At 25°C and 65% humidity, the sample and several commercially available products (control samples) were cut into 2*5cm samples, and the upper and lower surface film materials were removed and weighed and recorded as W. 0 , spread it on the surface of a glass dish, and measure the real-time weight W of the sample at regular intervals within 180 minutes, and calculate W and W 0 The water retention capacity of the sample was evaluated by the ratio of
[0083] Table 2 Water retention test data of hydrogel samples and commercially available samples
[0084]
[0085]
[0086] The hydrogel contains a large amount of water, which will partially evaporate when used under natural conditions, affecting the user experience. The more water is lost, the lower the product weight W, W / W 0 The above data show that after natural drying for 180 minutes at 25°C and 65%, the real-time weight still has 82.81% of the initial weight, which is close to the water-retaining capacity of commercially available control samples 2 and 3, and significantly higher than control sample 1. This shows that Example 1 is similar to control samples 2 and 3, and has good water-retaining capacity.
[0087] (4) Breathability
[0088] The samples were tested according to the water vapor transmission rate test standard YY / T 0148-2006, and the water vapor transmission rates of the samples were compared with those of several commercially available products (control samples).
[0089]
[0090] Compared with several commercially available samples, the samples prepared by this method have a higher water vapor permeability. The YY / T1627-2018 standard states that if a wound dressing claims to be "breathable", the water vapor permeability should be no less than 500g / (m 2 ·24h), which shows that the samples prepared by this method have excellent air permeability.
[0091] Example 2
[0092] A method for preparing a photopolymerized rapid-forming transparent medical hydrogel dressing comprises the following steps:
[0093] S1. Preparation of prepolymer solution
[0094] At room temperature, 35 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 5 parts of acrylamide, 10 parts of sodium acrylate, and 10 parts of sodium styrene sulfonate were placed in 100 parts of water and stirred to dissolve, and lactic acid was used to adjust the pH to 7.0. Then, 1 part of polyethylene glycol dimethacrylate (as a cross-linking agent), 0.05 parts of Irgacure 2959 (as a photoinitiator), 15 parts of propylene glycol (as a moisturizer), 0.3 parts of PHMB (as a preservative) and 0.01 parts of menthyl ester (as a functional agent) were added in sequence, and the mixture was fully stirred and dissolved to obtain a prepolymer solution containing ultraviolet light activity.
[0095] S2. Prepolymer coating and molding
[0096] Pour the prepolymer liquid containing UV light activity onto the conveyor belt of the coating equipment at a uniform speed, place a release film underneath, and cover the upper surface with a layer of anti-sticking film. After leveling, irradiate with 365nm UV light for 5s to form. The UV light intensity is 120mw / cm 2 , the coating thickness is 0.5mm.
[0097] S3. Die cutting
[0098] The semi-finished sheet-like hydrogel obtained by coating is cut through a mask-shaped mold to obtain a mask-shaped patch (such as Figure 2 shown).
[0099] Example 3
[0100] A method for preparing a photopolymerized rapid-forming transparent medical hydrogel dressing comprises the following steps:
[0101] S1. Preparation of prepolymer solution
[0102] At room temperature, 45 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 5 parts of acrylamide, 5 parts of sodium acrylate, and 8 parts of sodium styrene sulfonate were placed in 100 parts of water and stirred to dissolve, and citric acid was used to adjust the pH to 9.5. Then, 0.3 parts of polyethylene glycol diacrylate (as a cross-linking agent), 0.05 parts of Irgacure 2959 (as a photoinitiator), 10 parts of butanediol (as a moisturizer), 0.1-0.5 parts of phenoxyethanol (as a preservative) and 0.05 parts of camellia extract (as an efficacy agent) were added in sequence, and the mixture was fully stirred and dissolved to obtain a prepolymer solution containing ultraviolet light activity.
[0103] S2. Prepolymer coating and molding
[0104] Pour the prepolymer liquid containing UV light activity onto the conveyor belt of the coating equipment at a uniform speed, place a release film underneath, and cover the upper surface with a layer of anti-sticking film. After leveling, irradiate with 365nm UV light for 12s to form. The UV light intensity is 80mw / cm 2 , coating thickness is 1.5mm.
[0105] S3. Die cutting
[0106] The semi-finished sheet-like hydrogel obtained by coating is cut through a four-leaf clover-shaped die to obtain a four-leaf clover-shaped patch (such as Figure 2 shown).
[0107] Example 4
[0108] A method for preparing a photopolymerized rapid-forming transparent medical hydrogel dressing comprises the following steps:
[0109] S1. Preparation of prepolymer solution
[0110] At room temperature, 20 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 15 parts of acrylamide, 5 parts of sodium acrylate, and 5 parts of sodium styrene sulfonate were placed in 100 parts of water and stirred to dissolve, and tartaric acid was used to adjust the pH to 9.0. Subsequently, 0.8 parts of polyethylene glycol dimethacrylate (as a cross-linking agent), 0.05 parts of LAP (as a photoinitiator), 20 parts of propylene glycol (as a humectant), 0.4 parts of benzethonium chloride (as a preservative) and 0.15 parts of allantoin (as a functional agent) were added in sequence, and the mixture was fully stirred and dissolved to obtain a prepolymer solution containing ultraviolet light activity.
[0111] S2. Prepolymer coating and molding
[0112] Pour the prepolymer liquid containing UV light activity onto the conveyor belt of the coating equipment at a uniform speed, place a release film underneath, and cover the upper surface with a layer of anti-sticking film. After leveling, irradiate with 365nm UV light for 8s to form. The UV light intensity is 40mw / cm 2 , coating thickness is 1.0mm.
[0113] S3. Die cutting
[0114] The semi-finished sheet-shaped hydrogel obtained by coating is cut through a crescent-shaped mold to obtain a crescent-shaped patch.
[0115] Example 5
[0116] A method for preparing a photopolymerized rapid-forming transparent medical hydrogel dressing comprises the following steps:
[0117] S1. Preparation of prepolymer solution
[0118] At room temperature, 20 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 5 parts of acrylamide, 10 parts of sodium acrylate, and 8 parts of sodium styrene sulfonate were placed in 100 parts of water and stirred to dissolve, and lactic acid was used to adjust the pH to 7.5. Subsequently, 0.8 parts of polyethylene glycol dimethacrylate (as a cross-linking agent), 0.05 parts of LAP (as a photoinitiator), 15 parts of glycerol (as a moisturizer), 0.25 parts of PHMB (as a preservative) and 0.11 parts of rose oil (as a functional agent) were added in sequence, and the mixture was fully stirred and dissolved to obtain a prepolymer solution containing ultraviolet light activity.
[0119] S2. Prepolymer coating and molding
[0120] Pour the prepolymer liquid containing UV light activity onto the conveyor belt of the coating equipment at a uniform speed, place a release film underneath, and cover the upper surface with a layer of anti-sticking film. After leveling, irradiate with 365nm UV light for 10s to form. The UV light intensity is 70mw / cm 2, coating thickness is 3mm.
[0121] S3. Die cutting
[0122] The semi-finished sheet-shaped hydrogel obtained by coating is cut through a circular mold to obtain a circular patch.
[0123] Comparative Example 1
[0124] A method for preparing a transparent medical hydrogel patch comprises the following steps:
[0125] S1. Preparation of prepolymer solution
[0126] At room temperature, 20 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 5 parts of acrylamide, 10 parts of sodium acrylate, and 8 parts of sodium styrene sulfonate were placed in 100 parts of water and stirred to dissolve, and lactic acid was used to adjust the pH to 7.5. Subsequently, 0.8 parts of polyethylene glycol dimethacrylate (as a cross-linking agent), 0.05 parts of ammonium persulfate (as a thermal initiator), 15 parts of glycerol (as a moisturizer), 0.25 parts of PHMB (as a preservative) and 0.11 parts of rose oil (as a functional agent) were added in sequence, and the mixture was fully stirred and dissolved to obtain a prepolymer solution.
[0127] S2. Prepolymer coating and molding
[0128] Pour the prepolymer liquid into the mold, put a layer of release film at the bottom, cover the upper surface with a layer of anti-stick film, and after leveling, place it in a 60℃ environment to react for 18 hours to solidify and form. The injection thickness is 3mm.
[0129] S3. Die cutting
[0130] The semi-finished sheet-shaped hydrogel obtained by coating is cut through a circular mold to obtain a circular patch.
[0131] Comparative Example 2
[0132] A method for preparing a transparent medical hydrogel patch comprises the following steps:
[0133] S1. Preparation of prepolymer solution
[0134] At room temperature, 20 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 5 parts of acrylamide, 10 parts of sodium acrylate, and 8 parts of sodium styrene sulfonate were placed in 100 parts of water and stirred to dissolve, and lactic acid was used to adjust the pH to 7.5. No crosslinking agent was added, 0.05 parts of LAP (as a photoinitiator), 15 parts of glycerol (as a moisturizer), 0.25 parts of PHMB (as a preservative) and 0.11 parts of rose oil (as a functional agent) were added, and the mixture was fully stirred and dissolved to obtain a prepolymer solution.
[0135] S2. Prepolymer coating and molding
[0136] The prepolymer liquid was poured uniformly onto the conveyor belt of the coating equipment, with a release film underneath and an anti-sticking film on the top. After leveling, it was still not formed after being irradiated with 365nm ultraviolet light for 1 hour. The intensity of the ultraviolet light was 70mw / cm 2 , coating thickness is 3mm.
[0137] S3. Die cutting
[0138] The coating did not produce a semi-finished sheet-like hydrogel, and the die-cutting was impossible.
[0139] Comparative Example 3
[0140] A method for preparing a transparent medical hydrogel patch comprises the following steps:
[0141] S1. Preparation of prepolymer solution
[0142] At room temperature, 20 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 5 parts of acrylamide, 10 parts of sodium acrylate, and 8 parts of sodium styrene sulfonate were placed in 100 parts of water and stirred to dissolve, and lactic acid was used to adjust the pH to 7.5. Then, 0.8 parts of polyethylene glycol dimethacrylate (as a cross-linking agent), no photoinitiator, 15 parts of glycerol (as a moisturizer), 0.25 parts of PHMB (as a preservative) and 0.11 parts of rose oil (as a functional agent) were added in sequence, and the mixture was fully stirred and dissolved to obtain a prepolymer solution.
[0143] S2. Prepolymer coating and molding
[0144] The prepolymer liquid was poured uniformly onto the conveyor belt of the coating equipment, with a release film underneath and an anti-sticking film on the top. After leveling, it was still not formed after being irradiated with 365nm ultraviolet light for 1 hour. The intensity of the ultraviolet light was 70mw / cm 2 , coating thickness is 3mm.
[0145] S3. Die cutting
[0146] The coating did not produce a semi-finished sheet-like hydrogel, and the die-cutting was impossible.
[0147] From Example 1 to Example 5, the transparent medical hydrogel patch prepared therein can be completely formed in the molding process after UV polymerization for only 5-15s, and the light polymerization efficiency is significantly improved; while the transparent medical hydrogel patch of Comparative Document 1 needs to react in a 60°C environment for 18h to cure before it can be formed; the transparent medical hydrogel patches of Comparative Documents 2 and 3 still cannot be formed after 1h of UV light irradiation during the molding process.
[0148] The above is a specific description of the preferred implementation of the present application, but the invention of the present application is not limited to the described embodiments. Technical personnel familiar with the field can also make various equivalent modifications or substitutions without violating the spirit of the present application. These equivalent modifications or substitutions are all included in the scope defined by the claims of the present application.
Claims
1. A photopolymerized rapid prototyping transparent medical hydrogel patch, characterized in that: It comprises a hydrogel; the hydrogel is prepared by coating a prepolymer liquid containing ultraviolet light activity on a release film and then polymerizing and molding it through ultraviolet light irradiation.
2. The transparent medical hydrogel patch according to claim 1, characterized in that: The prepolymer solution containing ultraviolet light activity comprises the following raw materials in parts by weight: 10-45 parts of 2-acrylamide-2-methylpropanesulfonic acid sodium salt, 5-30 parts of acrylamide, 5-10 parts of sodium acrylate, 5-10 parts of sodium styrene sulfonate, 0.15-1.5 parts of cross-linking agent, 0.01-0.1 parts of photoinitiator, 5-30 parts of moisturizing agent, 0.1-0.5 parts of preservative, and 0.01-0.2 parts of efficacy agent.
3. The transparent medical hydrogel patch according to claim 2, characterized in that: The cross-linking agent is at least one of polyethylene glycol diacrylate and polyethylene glycol dimethacrylate.
4. The transparent medical hydrogel patch according to claim 2, characterized in that: The photoinitiator is at least one of TPO, Irgacure 2959 and LAP.
5. The transparent medical hydrogel patch according to claim 2, characterized in that: The moisturizing agent is at least one of glycerin, propylene glycol and butylene glycol.
6. The transparent medical hydrogel patch according to claim 2, characterized in that: The preservative is at least one of methylparaben, PHMB, benzethonium chloride and phenoxyethanol.
7. The transparent medical hydrogel patch according to claim 2, characterized in that: The efficacy agent is at least one of sodium hyaluronate, menthyl ester, camellia extract, allantoin and rose oil.
8. The transparent medical hydrogel patch according to claim 1, characterized in that: The process of coating on the release film is to pour the prepolymer liquid containing ultraviolet light activity onto the conveyor belt of the coating equipment, and the thickness of the prepolymer liquid coated with ultraviolet light activity is 0.5-3mm; after leveling, it is irradiated with ultraviolet light to form.
9. The transparent medical hydrogel patch according to claim 1 or 8, characterized in that: The ultraviolet light irradiation polymerization molding is molding by ultraviolet light irradiation for 5-15s.
10. A method for preparing a photopolymerized rapid-prototyping transparent medical hydrogel patch according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preparation of prepolymer solution Weigh the raw materials of the prepolymer liquid containing ultraviolet light activity by mass; put 10-45 parts of 2-acrylamide-2-methylpropane sulfonic acid sodium salt, 5-30 parts of acrylamide, 5-10 parts of sodium acrylate, and 5-10 parts of sodium styrene sulfonate in 100 parts of water and dissolve them to obtain a mixed solution A; adjust the pH of the mixed solution A to 7-10; add 0.15-1.5 parts of a crosslinking agent, 0.01-0.1 parts of a photoinitiator, 5-30 parts of a moisturizer, 0.1-0.5 parts of a preservative, and 0.01-0.2 parts of a functional agent into the mixed solution A with the pH adjusted and dissolve them to obtain a prepolymer liquid containing ultraviolet light activity; S2. Prepolymerization liquid coating Pour the prepolymer liquid containing ultraviolet light activity onto the conveyor belt of the coating equipment, and the thickness of the ultraviolet light activity prepolymer liquid is 0.5-3mm; after leveling, it is irradiated with ultraviolet light to form; S3. Molding After being irradiated with ultraviolet light for 5-15 seconds, a semi-finished sheet of hydrogel is obtained; S4. Die cutting The semi-finished sheet of hydrogel is die-cut to obtain a transparent medical hydrogel patch.
Citation Information
Patent Citations
Preparation method of hydrogel repair mask and product thereof
CN115944579A
High-tensile, strong-adhesion and high-ionic-conductivity hydrogel and preparation method thereof
CN117343359A
Preparation method of super-hydrophilic high-transparency hydrogel mask
CN117598912A